HUBUNGAN PERSEPSI PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK BERBANTUAN MEDIA YOUTUBE DAN MOTIVASI BELAJAR DENGAN KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS VII SMPN 11 KABUPATEN SORONG TAHUN PELAJARAN 2024/2025 - Purwiyati Purwiyati; D. B. Putut Setiyadi; Triyono; Hersulastuti; Nanik Herawati (Qalam : Jurnal Ilmu Kependidikan, 2025)
This study aims to: 1) assess the relationship between the application of project-based learning model assisted by YouTube media and the ability to write procedural texs of grade VII students of SMPN 11 Sorong Regency. 2) assess the relationship between learning motivation and the ability to write procedural texts of grade VII students of SMPN 11 Sorong Regency, and 3) identify the relationship between the perception of the application of project-based learning model assisted by Youtube media and learning motivation with the ability to write procedural texts of grade VII students of SMPN 11 Sorong Regency. The study used a quantitative correlation approach, the population amounted to 103 people throughout class VII with a research sample of 34 students. The collection technique used multi-stage sampling and measuring instruments with questionnaires and learning outcomes tests and supported by observation and documentation. Data were analyzed using simple linear regression and multiple linear regression with SPSS software. The results showed that: 1)there is a significant relationship between the application of Youtube-assisted PjBL model (X₁) and the ability to write procedure text (Y) with 0,000 ˂ 0,05. 2) there is a significant relationship between learning motivation variables and the ability to write procedure text, with sig. 0,000 ˂ 0,005 and 3) simultaneously, there is a significant relationship between (X₁) and (X₂) with (Y) in multiple regression that sig. value 0,000 ˂ 0,05. This proves that there is a significant relationship between the perception of the application of the PjBL model assisted by Youtube media and learning motivation wit the ability to write procedural texts of seventh grade students of SMPN 11 Sorong Regency.